CONTRIBUTION SUFISM AL GHAZALI IN MULTICULTURAL SOCIETY - Yusuf, Achmad (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan)
While the contribution of Sufism al-Ghazali in a Multicultural Society;  First, he presents a doctrine gentle and polite, not Islam that is hard and curt. God is not only presented as the One who firmly as is commonly stated jurists, but also God the Merciful and Most Merciful. Second, the steps of the intellectual life of Imam al-Ghazali gives a lesson in the process of finding the truth. As far as can be read in his autobiography, he did not seem to impose themselves as Sufis from the beginning. Long before written books of Sufism, such as the Ihya' Ulumalddin, Imam al-Ghazali pursue and poor across the various disciplines of business development, such as the logic-philosophy, Jurisprudence-usul fiqh, and theology-kalam. Third, Ihya' Ulumalddin is written to reduce the dose of formalism-legalism in the body of Muslims at that time. Formalism in the pro-Islam Imam al-Ghazali feared would eliminate the moral-ethical teachings. This is because Imam al-Ghazali increasingly upset with moral-ethical decline of the scholars at the time. For him, the Islamic sciences is not a means to pursue the interests of the world as to gain popularity and authority (al-shuhrahlinayl),but to build the sublime morals and probity. That is why, in the book Ihya' Ulumalddin, he did not hesitate to criticize 'ulama'sufi  (clerical nefarious) that makes knowledge as barter to get a throne and wealth. Fourth, doctrinally, Imam al-Ghazali Sufism could provide a solution to the tendency of a multicultural society who feel alienated and psychologically suffer in isolation it. That one feels threatened by the other, both socially and economically and politically. Other people considered enemies. In fact, nothing is more needed today than the ability to memperlakukaan others as ourselves and not as opponents. Imam al-Ghazali invites us to balance physical activity with spiritual contemplation.